Implicit Racial and Gender Bias About Handguns: A New Implicit Association Test - Ellyson, Alice M. (Journal of interpersonal violence, 2023)
This study measured implicit and explicit racial bias about women and handguns and addressed important perceptions and stereotypes about gun competence and victimization that vary based on race and gender. We administered a national survey to 1,000 US adults using a new Race–Women–Handguns Implicit Association Test (IAT). Survey weighting was used to generate nationally representative estimates on the prevalence of implicit racial bias about women with handguns. The majority of participants (62.5%) associated Black women with handguns and White women with smartphones (weighted-mean IAT = 0.252; 95% CI [0.227, 0.276]) reflecting an anti-Black bias among US adults that is stereotype consistent associating Black women with handguns and White women with smartphones. The proportion that indicated Black and White women were competent with handguns was low (21.6% and 22.4%, respectively), and the proportion of US adults who indicated Black women are more likely to experience intimate partner violence (range: 19.4%−22.9%) and sexual harassment/assault (range: 11.4%−20.4%) was low compared to the prevalence of both forms of violence US among Black women that may impact the decision to possess a handgun. These findings suggest there is an anti-Black implicit bias about women with handguns (associating Black women with handguns) among US adults and support the need for further research measuring racism in systems and structures that intersect with gun possession.